Left anterior descending coronary artery obstruction. Clinical, electrocardiographic, and angiographic correlates. - Berndt, T (1976)
Seventy-six patients with severe (greater than 80%) occlusive left anterior descending coronary artery disease by coronary angiography were examined for the electrocardiographic characteristics of this disease in the presence (group A 59 patients) or the absence (group B 17 patients) of anterior wall asynergy (akinesis or dyskinesis). The incidence of clinically documented anterior myocardial infarction in these two groups of patients was examined. The collateral circulation to the left anterior descending coronary artery was also examined in the groups of patients with and without anterior wall asynergy. Thirty-eight of 59 (64%) patients with anterior wall asynergy (group A) showed electrocardiographic signs of anterior myocardial infarction, 17 per cent showed probable electrocardiographic signs of anterior myocardial infarction and 19 per cent showed no electrocardiographic signs. None of the 17 patients without anterior wall asynergy (group B) showed electrocardiographic signs of anterior myocardial infarction. In group A 74.6 per cent had documented clinical evidence of previous anterior myocardial infarction. Collateral filling of the distal left anterior descending coronary artery was seen in 71 per cent of group A and 100 per cent of group B patients. There was a significantly higher incidence (P = 0.02) of collateral filling in the patients without electrocardiographic evidence of definite anterior myocardial infarction (93% of 28 patients), than in those who showed definite electrocardiographic evidence of anterior myocardial infarction (66% of 38 patients).it is concluded that severe occlusive left anterior descending coronary artery disease with anterior wall myocardial asynergy is usually associated with electrocardiographic signs of anterior myocardial infarction, whereas equally severe left anterior descending coronary artery disease without anterior wall asynergy is rarely associated with electrocardiographic abnormalities of anterior myocardial infarction. Severe left anterior descending coronary artery obstruction without electrocardiographic and angiographic evidence of anterior myocardial infarction is usually associated with collateral circulation to the left anterior descending coronary artery and collateral circulation to the left anterior descending coronary artery is present less frequently when obstruction is associated with anterior myocardial infarction.